Design of a workstation based on a human-interfacing robot for occupational health and safety. - Yu, Ke; Zhang, Liyun; Zhang, Yanling; Yu, Qian; Li, Xiaohong; Krishnamoorthy, Sujatha; Kumar, Priyan Malarvizhi; Pandey, Hari Mohan; Srivastava, Gautam (Work, 2021)
BACKGROUND: Robots communicate with the physical world program with the mechanic's simulations. They recommend that people-to-people robotics will prepare for cognitive models. Presently, there is a considerable concern for greater flexibility and efficiency in the scope of human-robot interfacing collaboration across hospitals. Nevertheless, interfacing is still in its infancy in manufacturing; industrial practitioners have many questions and doubts about the efficiency of the device and the health of human operators. OBJECTIVES: Therefore, research on processes and methods of design is required to ensure that the intended human-computer interaction-based workstations effectively meet system performance, human safety, and ergonomics standards for realistic applications. This study provides a design process for a workstation appropriate for occupational health and safety. This article outlines the perspectives learned from incorporation into the preparation and operation of robotics of digital cognitive models. RESULTS: This ends with an overarching game-theoretical model of contact and analyses how different approaches contribute to effective communicating activities for the robot in its interaction with people. CONCLUSION: The new feature of this design process is the approach for testing alternative workstation designs, taking into account efficiency and safety features with computer simulations.